The enigmatical manipulators in the capsule synthesis of pasteurella multocida: iron acquisition proteins - Asli Balevi; Aysegul Ilban; Ali Uslu; Zafer Sayin; Ayten Gok; Beatriz Padron; Eda Toslak; Osman Erganis (Eurasian Journal of Veterinary Sciences)
Aim: Spontaneous capsular loss or capsular changes in Pasteurella multocida can result from repeated laboratory passages, positive or negative regulatory genes, or an unknown gene. This study, it was aimed to compare the properties of phenotypic, genotypic, and biotypic of each non-typical, and typical Pasteurella multocida strain, to determine the dominant genes on capsule synthesis. Materials and Methods: Fifty-six strains, which capsular type was determined, and thirty -six, which capsular type was not determined, were used in this study. Multiple linear regression analysis was used based on the presence of dominant genes (serogroup, serotype, toxin, adhesin, iron acquisition, and protectin) in the isolates. Results: When colony morphologies of strains were evaluated of these strains by culture methods, mucoid colony formation was commonly detected in typical strains (87.5%), in contrast to non-typical strains (27.7%). In typical strains, the highest percentages of ptfA, ompA, and tadD genes were 78.57%, 75%, and 69.64%, respectively. In non-typical strains, the highest rates of ompA, ptfA, and tadD genes were 61.1%, 52.78%, and 52.78%, respectively. According to multiple linear regression analysis results, the together hgbA with hgbB genes caused the increase of capsule synthesis in these strains. The presence of the ompA gene in these strains was secondly a induction on these strains. Other genes were not effective in capsule synthesis in these strains. Conclusion: It was determined that the most significant effect in the forming of non-typical P. multocida strains was related to not enough HgbA and HgbB genes. It was supposed that P. multocida may not be heavily encapsulated under iron-restricted conditions. Consequently, P. multocida may change its capsule or lose its capsule related to iron acquisition proteins.